Effect of Obesogenic Medications on Weight‐Loss Outcomes in a Behavioral Weight‐Management Program. Issue 5 (23rd April 2019) - Desalermos, Athanasios; Russell, Baylee; Leggett, Cecilia; Parnell, Amelia; Ober, Kathleen; Hagerich, Kelley; Gerlan, Cindy; Ganji, Gelareh; Lee, Euyhyun; Proudfoot, James A.; Grunvald, Eduardo; Gupta, Samir; et al.
Abstract : Objective: This study aimed to evaluate a possible association between the use of obesogenic medications and inadequate weight loss in a behavioral weight‐management program. Methods: This is a case‐control, single‐center study of 666 adult patients within a Veterans Health Administration health system who participated in the MOVE! behavioral weight‐loss program. The cohort was divided into responders ( n = 150), patients who achieved ≥ 5% total weight loss by the end of the MOVE! program, and nonresponders ( n = 516), those who achieved < 5% total weight loss. We reviewed each patient's medical records for exposure to obesogenic medication during the time of treatment. Results: Approximately 62% ( n = 411) of patients entering MOVE! had a prescription for obesogenic medications. Obesogenic medication use was associated with worse weight‐loss outcomes, and participants were 37% less likely to achieve a clinically meaningful (≥ 5% total weight loss) outcome at the end of the MOVE! program (odds ratio, 0.633; 95% CI: 0.427‐0.937; adjusted P = 0.022). Patients who received three or more medications ( n = 72) had the greatest difficulty achieving 5% weight loss compared with the control group (odds ratio, 0.265; 95% CI: 0.108‐0.646; adjusted P = 0.003). Conclusions: The use of provider‐prescribed obesogenic medications was associated with worse weight‐loss outcomes in a behavioral weight‐loss program. Closer scrutiny of patient medications is necessary to help improve outcomes of weight‐loss treatments.